Legal Awareness of Citizens in Preventing Forest and Land Fires (Karhutla) in South Kalimantan Province - Akhyar, Zainul; Kiptiah, Mariatul; Ruchliyadi, Dian Agus; Elmy, Muhammad (Journal of Ecohumanism, 2024)
This article is based on an empirical study of forest and land fires in South Kalimantan Province. These fires frequently occur and persist, especially during drought seasons. The main causes are twofold: first, the expansion of agricultural land through clearing new areas; and second, the negligence of residents during hot, dry seasons, such as discarding cigarette butts carelessly without considering the potential consequences. The root issue behind these fires is the low level of legal awareness among citizens. This lack of awareness is due to the low educational levels of residents living near fire-prone areas, as well as insufficient and poorly structured government-led socialization efforts. Additionally, the economic conditions of these communities, where many are low-income farmers, contribute to their reliance on traditional, quick, and cost-effective methods like burning to manage land for agriculture. This practice not only harms the environment but also impacts public health. Therefore, effective measures to address forest and land fires require a dual approach from the authorities: enhancing legal awareness through improved socialization efforts and addressing the economic challenges faced by residents in fire-affected areas.